Pengaruh Relaksasi Otot Progresif Terhadap Kadar Gula Darah Pasien Diabetes Melitus Tipe II di RSUD Karanganyar - Hidayah, Ririn Nurul; Husain, Fida'; Sutarwi, Sutarwi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
The prevalence of Diabetes Mellitus in Central Java is 1.59% or around 91,161 people. In Karanganyar Regency there are 2% of people with diabetes mellitus or around 2,322 people of the total population. In people with diabetes mellitus to reduce vascular complications, neuropathy, and to achieve normal blood glucose levels by doing physical exercise. One of the physical exercises is by providing progressive muscle relaxation exercises. Knowing the results of implementing progressive muscle relaxation on blood sugar levels in patients with type II diabetes mellitus at Karanganyar Hospital. This research is a descriptive research with a case study approach. Implementation was carried out 3 times for 3 consecutive days. There was a decrease in blood sugar levels after doing progressive muscle relaxation exercises. The first day of the respondent Mr. R had a blood sugar level of 244 mg/dl after implementation to 216mg/dl. Respondent Mrs. W sugar content from 368 mg/dl to 349 mg/dl. Respondent Mr. R on the first day to the third day had a difference in blood sugar levels of 28-30 mg/dl, and the respondent Mrs. From the first day to the third day, the difference in blood sugar levels was 19-22 mg/dl. Respondent Mr. R has a more significant difference in the blood sugar level score compared to the respondent Ny. W after progressive muscle relaxation.